Sensitivity Analysis of Attitudes, Perceptions of Presence, and Personality Characteristics toward Virtual Merchandising - Julie Becker; Al Bellamy (New Horizons in Education and Social Studies Vol. 9, 2021)
This study explored the belief that individual personality traits affect one’s disposition toward shopping within a virtual environment. The goal of this paper has been achieved by studying the relationship between an individual’s perception of presence within a virtual merchandising environment and their attitudes toward virtual shopping. Symbolic interactionism was used as the theoretical framework and utilizing four of the Big Five personality framework: 1) openness, 2) conscientiousness, 3) extraversion, and 4) neuroticism. It also examined whether an individual’s personality affected their attitude toward virtual shopping along with the relationship between presence and attitudes toward online shopping. The study was conducted among undergraduate students enrolled in an Apparel Textiles and Merchandising Program at a university located in Michigan. The data analysis indicated a positive correlation between perceptions of presence and an individual’s willingness to make purchases within an online shopping environment as well as their overall satisfaction with shopping in such an environment. Two of the personality factors from the Big Five personality framework, neuroticism and extroversion, were shown to moderate these relationships. While the results confirmed that in a virtual environment, one’s personality traits affect individual’s disposition toward shopping, it is critical to study the shift in attitude as the traditional brick and mortar stores diminish.